Application of Slow Deep Breathing Therapy in Reducing the Scale of Pain in Post Section Caesarea Mothers in Jasmine Room, dr. Soediran Mangun Sumarso Regional Hospital, Wonogiri - Indri Magfiroh Rahmawati; Zulfa Mahdiatur Rasyida; Sumardi (Jurnal Kesehatan Komunitas Indonesia, 2025)
Background: Sectio caesarea (SC) is the act of removing the baby through an incision in the abdominal wall and uterus to save the mother and baby for several medical indications. Patients who undergo childbirth by SC usually feel various discomforts in the form of pain. One of the non-pharmacological actions that can be done to reduce pain is slow deep breathing. Objective: To find out the results of the slow deep breathing technique in reducing the pain scale in post-SC mothers in the Jasmine Room of dr. Soediran Mangun Sumarso Regional Hospital, Wonogiri. Methods: The research design used is a descriptive case study. Results: The application of the slow deep breathing technique for 2 days resulted in a decrease in the postoperative pain scale. In Mrs. Y, the postoperative pain scale with a pain scale of 7 (severe pain), the pain dropped to a scale of 3 (mild pain), while in Mrs. M the postoperative pain scale with a pain scale of 7 (severe pain) the pain dropped to a scale of 2 (mild pain). Conclusion: There was a decrease in the scale of post SC pain after the application of the slow deep breathing technique for 2 days